Pelaksanaan Pembelajaran Komunikasi Non-verbal Bahasa Arab dengan Bahasa Tubuh sebagai Pemahaman Kinesik Lintas Budaya - Isma'il (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Arabic is a universal language, Learning Arabic cannot be separated from the social and environmental environment that surrounds it. Learning Arabic requires adaptation to the environment which is an integral part of educational institutions. Students are part of the learning process, after formal education is complete, then they again become one of the important elements in society. Non-verbal language is statement forms of personality or personality traits that are manifested in body movements. Arabic is also an interesting study, where Arabic is one of the dominant Semitic languages and still persists today. Based on the focus of the study, this study aims to describe: The Implementation of Learning Arabic non-verbal communication with Body Language as a cross-cultural kinesic understanding. This research is